Middle Eocene to Late Oligocene Antarctic glaciation/deglaciation and Southern Ocean productivity. (21st March 2014) - Villa, Giuliana; Fioroni, Chiara; Persico, Davide; Roberts, Andrew P.; Florindo, Fabio
Abstract During the Eocene‐Oligocene transition, Earth cooled significantly from a greenhouse to an icehouse climate. Nannofossil assemblages from Southern Ocean sites enable evaluation of paleoceanographic changes and, hence, of the oceanic response to Antarctic ice sheet evolution during the Eocene and Oligocene. A combination of environmental factors such as sea surface temperature and nutrient availability is recorded by the nannofossil assemblages of and can be interpreted as responses to the following changes. A cooling trend, started in the Middle Eocene, was interrupted by warming during the Middle Eocene Climatic optimum and by short cooling episodes. The cooling episode at 39.6 Ma preceded a shift toward an interval that was dominated by oligotrophic nannofossil assemblages from 39.1 to 36.2 Ma. We suggest that oligotrophic conditions were associated with increased water mass stratification, low nutrient contents, and high efficiency of the oceanic biological pump that, in turn, promoted sequestration of carbon from surface waters, which favored cooling. After 36.2 Ma, we document a large synchronous surface water productivity turnover with a dominant eutrophic nannofossil assemblage that was accompanied by a pronounced increase in magnetotactic bacterial abundance. This turnover reflects a response of coccolithophorids to changed nutrient inputs that was likely related to partial deglaciation of a transient Antarctic ice sheet and/or to iron delivery to the sea surface. Eutrophic conditions were maintained throughout the Oligocene, which was characterized by a nannofossil assemblage shift toward cool conditions at the Eocene‐Oligocene transition. Finally, a warm nannofossil assemblage in the Late Oligocene indicates a warming phase.